AIESEC Global Volunteer Activities and Students’ Speaking Confidence - Mely Yanti; Clarry Sada (FKIP - Universitas Tanjungpura, 2023)
This study intends to analyze the activities carried out by learners during their participation in the AIESEC Global Volunteer Program on their speaking confidence. Additionally, it seeks to provide an explanation regarding how these activities contribute to the enhancement of learners' speaking confidence. The research conducted is a qualitative case study, with three participants who have undergone the AIESEC Global Volunteer Program being the subjects of this study. This research was done by interviewing all the participants and collecting artifacts from the program. The result of this research was that all participants appeared to be so confident in answering the interview questions and expressing themselves. Besides, all the participants stated that the program of AIESEC Global Volunteer Activities indeed brought their confidence to the next level. In other words, during the program, they experienced so many pieces of training that it was believed that those activities contributed to the improvement of their speaking confidence.